VISUALIZAÇÃO DE DADOS VOLUMÉTRICOS COMPRIMIDOS BASEADO NA TRANSFORMADA DO COSSENO LOCAL - Demetrio, Fernando Jorge Cutrim (2005)
This work describes the development of an algorithm for visualization of compressed volumetric data with a local cosine transform scheme, that minimizes the blocking artefacts generated by transform compression methods, and makes possible the visualization of large volume data in computer with limited memory resources. We also present the results obtained for the visualization process .